2012
DOI: 10.1523/jneurosci.6481-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Stimulation Depresses the Primate Anterior-Cingulate-Cortex and Prevents Spontaneous Recovery of Aversive Memories

Abstract: Functional abnormalities in the dorsal-anterior-cingulate-cortex (dACC) underlie anxiety disorders and specifically post-traumatic stress disorder (PTSD). Promising and common behavioral approaches have limited effectiveness and many subjects exhibit spontaneous recovery of fear, as also evident in animal models following extinction training. Here, we use low-frequency stimulation (LFS), a protocol shown to induce long-term depression, with the aim of affecting synaptic plasticity induced by fear acquisition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 74 publications
3
41
0
Order By: Relevance
“…Based on this neuronal circuitry, one speculation would be that inactivating the PL cortex during reconsolidation attenuates the input to the basolateral nucleus of the amygdala and/or hippocampus, brain hubs that modulate the maintenance of emotional memories charged with negative valence (Nader et al 2000;Debiec et al 2002;Lee et al 2004Lee et al , 2006Parsons et al 2006;Tronson et al 2006;de Oliveira Alvares et al 2008;Rehberg et al 2010;Giachero et al 2013). Of note, the rat PL cortex has a similar anatomy and connectivity to that of the primate dorsal anterior cingulate cortex (McDonald 1998;Stefanacci and Amaral 2002), which has a similar functional role in maintaining the original aversive memory (Klavir et al 2012). In humans, this area is suggested to be dysfunctional (commonly hyperactive) in anxiety disorders, such as post-traumatic stress (Fani et al 2012;Pitman et al 2012;Admon et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this neuronal circuitry, one speculation would be that inactivating the PL cortex during reconsolidation attenuates the input to the basolateral nucleus of the amygdala and/or hippocampus, brain hubs that modulate the maintenance of emotional memories charged with negative valence (Nader et al 2000;Debiec et al 2002;Lee et al 2004Lee et al , 2006Parsons et al 2006;Tronson et al 2006;de Oliveira Alvares et al 2008;Rehberg et al 2010;Giachero et al 2013). Of note, the rat PL cortex has a similar anatomy and connectivity to that of the primate dorsal anterior cingulate cortex (McDonald 1998;Stefanacci and Amaral 2002), which has a similar functional role in maintaining the original aversive memory (Klavir et al 2012). In humans, this area is suggested to be dysfunctional (commonly hyperactive) in anxiety disorders, such as post-traumatic stress (Fani et al 2012;Pitman et al 2012;Admon et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies performed in rodents and non-human primates used artificial stimulation protocols to induce LTP or LTD in prefrontal regions during fear extinction 99,100 . These studies showed that LTP-inducing stimulation in the rodent ILc or LTD-inducing stimulation in the monkey dorsal anterior cingulate cortex (dACC, an analog of the rodent PLc) both facilitate fear inhibition during extinction 99,100 . Together with studies presented above, these data suggest the existence of parallel pathways regulating fear expression.…”
Section: Bidirectional Control Of Fear Expression In Ban-dmpfc Circuitsmentioning
confidence: 99%
“…A working framework that has been established over the past decade suggests that fear expression and fear suppression are supported by different subdivisions of the mPFC. The more dorsal mPFC (called the prelimbic (PL) cortex in rodents and dorsal anterior cingulate (dACC) in primates) increases activity during fear conditioning and expression, whereas the ventral mPFC (called the infralimbc (IL) cortex in rodents and ventral mPFC (vmPFC) in primates) is active during expression of non-aversive associations or safety [56,57,58,59]. Accordingly, interactions of the more dorsal PFC with the BLA is suggested to support threat-related behavior [50,52,60,61], whereas the vmPFC is proposed to interact with the amygdala during fear suppression [61,62].…”
Section: Bla-mpfc Connectivity In Stimulus Discrimination: Acquisitionmentioning
confidence: 99%
“…Importantly, in addition to processing aversive stimuli, the dACC/PL is a prominent region for response adjustment in a broad range of circumstances when cues change their meaning [57,65,66]. Cue discrimination in the mPFC is likely shaped by convergent inputs from multiple cortical as well as subcortical structures [67,68].…”
Section: Bla-mpfc Connectivity In Stimulus Discrimination: Acquisitionmentioning
confidence: 99%